Notes on the Uniqueness and Value Sharing for Meromorphic Functions Concerning Differential Polynomials - Li, Jin-Dong (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the problem of uniqueness of meromorphic functions concerning differential polynomials, and obtain some results. These results improve the results obtained earlier by Li [J. Sichuan Univ. (Natural Science Edition), 45, 21–24 (2008)] and Dyavanal [J. Math. Anal. Appl., 374, 335–345 (2011)].